Entrepreneurial Mindset of Generation Z: The Role of Self-Efficacy and Achievement Motivation in Entrepreneurship Education - Andi Tenri Ampa; Syamsu Rijal; Andi Caesar To Tadampali; Nurwahida Nurwahida; Wulan Purnamasari (FKIP Universitas Lampung, 2026)
This study aims to analyze and describe the influence of entrepreneurship education on Generation Z students' entrepreneurial mindset, with self-efficacy and achievement motivation as mediating variables. This study is a quantitative research type with the population in this study, namely: (1) domiciled or currently residing in Makassar, (2) aged 18–26 years, and (3) having an interest or experience in entrepreneurship educationactivities, either through formal education or through training, seminars, or independent experience. Determination of the number of samples using purposive sampling techniques, so that 141 research respondents were obtained. The research instrument was a Likert-scale questionnaire, and each item was developed by the researcher from the theoretical dimensions underlying the research variables. Data collection was carried out by distributing questionnaires online via a digital platform during June-July 2025. Of the 160 questionnaires distributed, 141 were returned, and all met the data validity requirements for further analysis. Data were analyzed using the SmartPLS application for Windows. Entrepreneurship educationhas a significant effect on achievement motivation and self-efficacy. Only achievement motivation has been proven to significantly mediate the relationship between entrepreneurship education and entrepreneurial mindset. Self-efficacy does not play a significant mediating role. This study shows that the most important factor in developing an entrepreneurial mindset is increasing achievement motivation in entrepreneurship education. In other words, developing an entrepreneurial mindset among Generation Z students should be directed not only to cognitive aspects but also to strengthening character and achievement motivationvalues. Keywords: entrepreneurship, self-efficacy, achievement motivation.